Abscisic acid alleviates harmful effect of saline–alkaline stress on tomato seedlings - Xu, Zijian; Wang, Jiachun; Zhen, Wentian; Sun, Tao; Hu, Xiaohui (Plant physiology and biochemistry, 2022)
Saline–alkaline stress inhibits plant growth and reduces yield. Abscisic acid (ABA) is an important plant hormone in response to plant stress. However, the role of ABA under saline–alkaline stress is poorly understood. Therefore, the mechanisms of ABA accumulation and resistance improvement in tomato seedlings were studied under saline–alkaline stress. We investigated whether ABA accumulation improved the saline–alkaline stress resistance ability of tomato. Here, wild-type (Solanum lycopersicum cv. Ailsa Craig) and ABA-deficient mutant (notabilis) seedlings were used to determine the membrane lipid peroxidation, osmotic substance and chlorophyll contents. ABA synthesis and signal transduction changes and ABA roles regulating the antioxidation in tomato seedlings subject to saline–alkaline stress were further explored. Results showed that ABA synthesis and signal transduction were induced by saline–alkaline stress. Under saline–alkaline stress, tomato seedlings had decreased relative water content, increased relative electrical conductivity and malondialdehyde content, and these changes were alleviated by exogenous ABA treatment. Exogenous ABA alleviated the degradation of chlorophyll in the leaves of tomato seedlings caused by saline–alkaline stress, further promoted the accumulation of proline and soluble sugar, reduced the content of ROS and improved the ability of the antioxidant enzyme system. Moreover, notabilis appeared to be sensitive to saline–alkaline stress. Overall, ABA is involved in the resistance of tomato seedlings to saline–alkaline stress, and exogenous ABA improves the saline–alkaline tolerance of tomato seedlings. •ABA synthesis and signal transduction were induced by saline-alkaline stress in tomato seedling.•Exogenous ABA alleviated harm of the saline-alkaline stress through regulating osmotic adjustment substances and chlorophyll.•ABA improved the ability of antioxidant enzyme system in short time, in ture removing excess ROS.